Postoperative Hospital Stay and Return to Normal Activity Following Laparoscopic Varicocelectomy at Kishwar Fazal Hospital Sheikhupura - Rizwan Ali Qaiser, Sikandar Hayat Gondal, Tariq Saeed, Shehroz Sikandar, Ghulam Murtaza Hiraj, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate mean postoperative hospital stay and return to normal activity after laparoscopic varicocelectomy at Kishwar Fazal Teaching Hospital Sheikhupura Method: A total of 45 diagnosed cases of clinically visible varicocele verified by U/S and infertility (primary, secondary) or scrotal discomfort were enrolled in the study from January 2020 uptill August 2022. After routine lab investigation, history and physical examination, the laparoscopic varicocelectomy was performed under general anesthesia, After the surgery done, we evaluated hospital stay subject to post operative pain on VAS and return to normal activity. Results: Of 45 cases, the mean age was 23.55+5.11 years, mean hospital stay was 1.92+0.84 days, mean duration of surgery was 39.48+3.69 minutes, and return to normal activity was 4.22+1.87 days. Conclusion: We concluded shorter hospital stay and early return to normal activity after the laparoscopic varicocelectomy is done. Keywords: Laparoscopic Varicocelectomy, hospital stay, return to normal activity